Erratum (Current Medicinal Chemistry, 2007)
In our review entitled ‘Myocardial Ischemia-Reperfusion Injury, Antioxidant Enzyme Systems, and Selenium: A Review’ in the Current Medicinal Chemistry, 2007, 14, 1539 -1549. We wish to correct a mistake in the authorship of the manuscript. It should be read as: Myocardial Ischemia-Reperfusion Injury, Antioxidant Enzyme Systems, and Selenium: A Review Kylie M. Venardos1, Anthony Perkins2, John Headrick2, David M. Kaye*,1 1Wynn Department of Metabolic Cardiology, Baker Heart Research Institut